Reducing Fuel Cell Degradation in Micro Combined Heat and Power Systems. Issue 8 (2015) - Zenith, Federico
Abstract: Fuel cells in domestic micro combined heat and power (μCHP) systems are subject to several degradation phenomena that can be counteracted with appropriate control strategies. Cost is an important factor, and additional equipment must be minimised. Controllers are proposed to counteract stack drying, flooding, poisoning by CO, and to estimate anodic hydrogen excess ratio to prevent hydrogen starvation. Tests on an emulator in LabVIEW indicate that the controllers are able to perform their function, and will be tested on a real system in 2015.